Benefits of Using Design Patterns on Microcontrollers in Implemented IoT Applications - Marek Babiuch; Petr Foltynek (Sensors)
As part of our research for microcontroller software support, we have developed a modular framework that utilizes previously unimplemented architectural principles for developing applications on microcontrollers. These principles are still a privilege of enterprise and server applications. The paper describes the benefits of a new architectural approach to developing applications on microcontrollers and describes the most common application scenarios along with examples of IoT application development using a framework with design pattern architecture and SOLID principles. As a result, our framework supports developers in creating robust, adaptive, and scalable applications. It emphasizes a modular and clean design that increases development efficiency and enables easy deployment of new features or integration of new technologies, such as new types of sensors, upgraded development boards, or improved development tools and frameworks. The architectural concepts offered useful guidance for creating applications ready for future challenges and changing technology environments, especially in the IoT area.